(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The article analyzes the socio-psychological characteristics of management decision-making in the leadership hierarchy. Knowing the psychological aspects of the decision-making process allows you to more effectively implement existing stages. The fact is that in order to make the right decision and implement it effectively, the leader must also psychologically follow certain actions. The main content of this event is that as the leader gathers information about the problem, he begins to create a primary perception of the problem - an information model. How compatible this model is with reality and the current situation depends on the fullness and completeness of the information being obtained.